ANALISIS PENGARUH CUSTOMER RETENTION PROGRAM (CRP) TERHADAP LOYALITAS MELALUI KEPUASAN NASABAH TABUNGAN PT. BNI 46, TBK CABANG JEMBER - Kurniawan, Dimas Firman; Suroso, Imam; Irawan, Bambang (JURNAL EKONOMI AKUNTANSI DAN MANAJEMEN, 2014)
This study aims to analize the effect of Customer Retention Effect Analysis Program (CRP) on Loyalty Through Customer Satisfaction in the Saving Customer atBNI 46 Jember. The purpose of this study is to determine and analyze 1); Customer Relationship Marketing influence on customewr satisfaction, 2); Influence After Sales Marketing Customer satisfaction; 3) Influence of Implicit Guarantee of customer satisfaction; 4) The influence of Unconditional Guarantee of customer satisfaction; 5) The influence of customer satisfaction Defection Management; 6) Zero Defects influence model of customer satisfaction; 7) Effect of Customer Relationship Marketing Customer Loyalty; 8) Influence of After Sales Marketing 9) Influence of Implicit Guarantee Customer Loyalty; 10) The influence of Unconditional Guarantee on Customer Loyalty; 11) Influence of Management Defection of Customer Loyalty; 12) Zero Defects influence Model of Customer Loyalty; 13) The influence of satisfaction on customer loyalty. The population is all of our PT. BNI 46 Tbk., Jember Branch throughout the region, which at the end of December 2012 has been recorded about 71.942 customers. Intake of the total sample using the method of sampling nonprobability (proportional stratefied sampling). The design of this study are included in the explanatory research and methods of analysis used is structural equation methods.Analysis result indicate that Customer Relationship Marketing and Unconditional Guarantee model is a program that has significant and positive relationship of loyalty in an effort to defend its customers, further After Sales Marketing, Implicit Guarantee, Defection Management and the worst compared to the six CRP program is Zero Defect Model